Pengaruh Kompetensi, Disiplin Kerja dan Work Life Balance Terhadap Kinerja Guru di Yayasan Pendidikan Rosma Karawang - Veronica Pangesti Indriyanti; Hartelina Hartelina; Nunung Nurhasanah; Sonny Hersona Gw (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of competence, work discipline, and work-life balance on teacher performance at the Rosma Education Foundation Karawang. Using a quantitative approach with questionnaires, data were obtained from 116 teachers and processed through multiple linear regression (SPSS 26). The findings show that competence and work-life balance have a positive and significant effect on teacher performance, while work discipline does not. Simultaneously, the three variables significantly influence performance with an R² of 0.608. The study emphasizes the importance of strengthening competence and maintaining work-life balance to enhance teacher performance.